R.P. Kumov and M. Gorky: History of Literary Relations (Proceedings of Southern Federal University. Philology, 2020)
The article deals with the history of literary relations of R.P. Kumov and M. Gorky. The correspondence of writers is analyzed, which reveals the role of M. Gorky in the creative biography of R.P. Kumov. Typological connections are established between M. Gorky’s novel «The Artamonov’s Affair» and R.P. Kumov’s drama «End of the Korostomyslov family».Key words: R.P. Kumov, M. Gorky, literary relations, creative biography.DOI 10.18522/1995-0640-2020-2-161-170